The automatic re-annotation of web images for improving access for blind users - Misman, Ahmad Fatzilah (2014)
The Internet has become the dominant means of communication in modern society. Increased use of and dependence on such things as email and the web has speeded up communication and allowed for a wide range of new ways in which we can communicate. The use of social media and Internet based shopping are amongst the most common forms of this development. Images are particularly common in such media. They are used for all sorts of purposes – from displaying products or pictures of individuals to decorations of all sorts. Blind people have the same rights and needs to use these modern technologies and so making sure that they can gain benefit from the images contained on these media is vital. The World Wide Web Consortium has drawn up specifications for the ways in which such images should be adaptable for best value by blind users. However, a large proportion of authors of web content do nothing to annotate the images they use in a way that would be of value to blind users.